Tick exposure biomarkers: A One Health approach to new tick surveillance tools - Dziedziech, Alexis; Krupa, Eva; Persson, Kristina E.M.; Paul, Richard; Bonnet, Sarah (Current research in parasitology & vector-borne diseases, 2024)
The spread of tick-borne disease (TBD) is escalating globally, driven by climate change and socio-economic shifts, underlining the urgency to improve surveillance, diagnostics, and control strategies. Ticks can transmit a range of pathogens increasing the risk of transmission of human and veterinary diseases such as Lyme disease, tick-borne encephalitis, theileriosis, anaplasmosis, or Crimean-Congo hemorrhagic fever. Surveillance methods play a crucial role in monitoring the spread of tick-borne pathogens (TBP). However, there are shortcomings in the current surveillance methods regarding risks related to ticks. Human-tick encounters offer a novel metric for disease risk assessment, integrating human behavior into traditional surveillance models. However, to more reliably measure tick exposure, a molecular marker is needed. The identification of antibodies against arthropod salivary proteins as biomarkers for vector exposure represents a promising avenue for enhancing existing diagnostic and surveillance metrics. Here we explore how the use of tick saliva biomarkers targeting recombinant proteins and synthetic peptides could significantly improve the assessment of TBD transmission risk and the effectiveness of vector control measures. With focused efforts on creating a biomarker against tick exposure suitable for humans and domestic animals alike, tick surveillance, diagnosis and control would be more achievable and aid in reducing the mounting threat of TBP through a One Health lens. [Display omitted] •A review focused on previous and current efforts in the development of tick salivary biomarkers.•Antibodies against tick saliva components are promising biomarkers for assessing tick exposure.•The review lists previously tested tick exposure biomarkers by both tick and host species.•Advances in biomarker discovery tools can provide new avenues for finding tick exposure biomarkers.